Deposition of organic matter and particulate nitrogen and phosphorus at the North Sea-Baltic Sea transition - a GIS study - Ditte L. Jansen; Dorte P. Lundqvist; Christian Christiansen; Lars C. Lund-Hansen; Thomas Balstrøm; Thomas Leipe (Oceanologia, 2003)
A GIS (Geographical Information System) based study on deposition in the North Sea-Baltic Sea transition area has been carried out. The study is based on (i) a digital bathymetry model, (ii) 93 available 210Pb / 137Cs sedimentation rate estimations, (iii) grain-size distributions, organic matter, C, N and P content of 64 top 1 cm sediment samples from the study area, and (iv) GIS-based modelling of resuspension potentials based on wind statistics. With the use of regression statistics on depth, resuspension potential and sediment characteristics, results are extrapolatedarea-wide from the 64 sampling positions. The area is divided into sediment types and classified as accumulation or erosion/transport bottoms. Model results show good agreement with existing maps of sediment distributions, indicating that the sediment distribution is governed to a large extent by wind-induced waves. Correlations of sediment types, their deposition rates and their N and P contents were used to estimate spatial deposition rates. In all, the yearly deposition in the study area amounts to 2.8 million tons of organic matter, 0.14 million tons of total nitrogen, and 0.035 milliontons of total phosphorus. Correlations of sediment types and dry bulk densities were used to infer spatial inventories of organic matter and total nitrogen and phosphorus in the top 1 cm of the sediments. A total of 100 million tons of organic matter, 4 million tons of total nitrogen, and 0.019 million tons of total phosphorus are contained in the top 1 cm of the sediments in the study area. In general, the deep parts of the study areawith low resuspension potentials act as sinks for the fine-grained sediments and their associated particulate nutrients.